Formation of the IGF1R/CAV1/SRC tri‐complex antagonizes TRAIL‐induced apoptosis in gastric cancer cells. (5th May 2017) - Guo, Tianshu; Xu, Ling; Che, Xiaofang; Zhang, Simeng; Li, Ce; Wang, Jin; Gong, Jing; Ma, Rui; Fan, Yibo; Hou, Kezuo; Zhou, Huiming; Hu, Xuejun; et al.
Abstract: Lipid rafts provide a biological platform for apoptosis induced by tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL). We previously reported that insulin‐like growth factor 1 receptor (IGF1R) translocation into lipid rafts helped to explain TRAIL resistance. However, it was not clear whether TRAIL resistance was caused by the interaction of IGF1R with caveolin‐1 (CAV1) and the non‐receptor tyrosine kinase SRC in lipid rafts of gastric cancer cells. Here, we observed high IGF1R expression in TRAIL‐resistant gastric cancer cells, and showed that IGF1R combined with both CAV1 and SRC in a native complex. TRAIL was shown to promote the formation of the IGF1R/CAV1/SRC tri‐complex and the activation of these three molecules. Knockdown of IGF1R or CAV1 or inhibition of SRC activity reduced the formation of this tri‐complex and enhanced TRAIL‐induced apoptosis. Furthermore, the overexpression of microRNA‐194 reversed TRAIL resistance by reducing IGF1R expression. In summary, TRAIL increased formation of the IGF1R/CAV1/SRC tri‐complex and the activation of downstream survival pathways, leading to TRAIL resistance in gastric cancer cells.